2013
DOI: 10.1177/000313481307900135
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Retroperitoneoscopic Adrenalectomy: Making a Good Procedure Even Better

Abstract: Posterior retroperitoneoscopic adrenalectomy (PRA) is a minimally invasive procedure offering several advantages over a transabdominal laparoscopic operation. The three-dimensional optics and articulating instrumentation offered by current robotic surgical technology potentially improve this procedure. Robotic-assisted PRA (RA-PRA) was performed in patients meeting standard criteria for minimally invasive adrenalectomy. We prospectively collected demographic, clinical, perioperative, and pathologic data on pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…Robotic surgery with a similar operation time and ergonomic improvements relative to laparoscopic surgery is attractive for surgeons, since robotic procedures offer more delicate dissection using endowrist and a magnified view. Robotic adrenalectomy may have advantages in maintaining a vascularized remnant during cortical sparing adrenalectomy [ 39 ]. However, it is unclear whether the substantial additional cost of the robotic procedure ($3,466 versus $2,737) is justified, since outcomes are equivalent [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robotic surgery with a similar operation time and ergonomic improvements relative to laparoscopic surgery is attractive for surgeons, since robotic procedures offer more delicate dissection using endowrist and a magnified view. Robotic adrenalectomy may have advantages in maintaining a vascularized remnant during cortical sparing adrenalectomy [ 39 ]. However, it is unclear whether the substantial additional cost of the robotic procedure ($3,466 versus $2,737) is justified, since outcomes are equivalent [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…From our systematic literature review we identified 18 studies which were eligible in our study. 10 of them were prospective [12,18,19,20,13,21,22,23,24,25] and 8 were retrospective [26,27,28,29,30,31,32,33]. Seven of these studies were conducted in USA, 5 in Korea, two in Italy, one in Taiwan, one in France, one in China and one was share between Italy and France.…”
Section: Resultsmentioning
confidence: 99%
“…Currently there are a number of reports concerning robot-assisted laparoscopic resection for adrenal tumors, such as PHEO ( 15 , 16 ). As the occurrence of extra-adrenal paraganglioma is rare, reports regarding this type of tumor are also uncommon, to the best of our knowledge, only Lehrfeld et al ( 14 ) have presented their experience of conducting a robot-assisted excision of a retroperitoneal mass in 2010.…”
Section: Discussionmentioning
confidence: 99%